2020
DOI: 10.1111/rda.13618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mineral supplementation on reproductive performance of pregnant cross‐breed Bonsmara cows: An experimental study

Abstract: Minerals in animal feed occur in variable structures, most of which determine the uptake and usage in biological processes in the body. Effective chemical breakdown of minerals may ensure efficient utilization in metabolism. The aim this study was to evaluate the effects of mineral supplementation on reproduction in cows. A farm was selected for the experiment due to the fact that it previously experienced different reproductive conditions in the farm. The farm comprises cross‐breed cows with Bonsmara dominati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The animal diet also affects the quantality of antioxidant in the seminal plasma that regulates the ROS level in ejaculated and frozen thaw semen responsible for protecting the sperm against cryoinjuries. Different research has shown the importance of mineral supplementation on health (Singh et al, 2019) [11] and reproductive performance of breeding animals (Molefe and Mwanza, 2020) [12] . During the experiment the animal maintained individually in the pan feeding were free to feed on the balanced ration offered to them while in the group feeding with common manger the animal might not have taken up the balance diet in accordance with the requirement of breeding buck.…”
Section: Resultsmentioning
confidence: 99%
“…The animal diet also affects the quantality of antioxidant in the seminal plasma that regulates the ROS level in ejaculated and frozen thaw semen responsible for protecting the sperm against cryoinjuries. Different research has shown the importance of mineral supplementation on health (Singh et al, 2019) [11] and reproductive performance of breeding animals (Molefe and Mwanza, 2020) [12] . During the experiment the animal maintained individually in the pan feeding were free to feed on the balanced ration offered to them while in the group feeding with common manger the animal might not have taken up the balance diet in accordance with the requirement of breeding buck.…”
Section: Resultsmentioning
confidence: 99%
“…Although cattle in group B had a significantly higher serum uric acid level, serum BUN level was not the highest. Although information on renal function indices of cattle supplemented with selenised yeast is limited, an earlier study showed that pregnant cows treated with a mineral mixture containing Se (5 mg/ml of sodium selenite), copper, zinc, manganese, calcium, magnesium, and phosphorus did not exhibit significant changes in the levels of serum urea/ BUN, uric acid, and transaminases (ALT, AST, and GGT) compared to untreated cows (Molefe and Mwanza, 2020). Therefore, these indices reflect a better health status of Xinjiang brown cattle fed different concentrations of selenised yeast.…”
Section: Discussionmentioning
confidence: 99%
“…Serum protein is part of the collection of amino acids in the body and indicates the nutritional status of livestock (Xuan et al, 2018). Molefe and Mwanza (2020) showed no difference in total blood protein by giving several doses of mineral. Khalil et al (2019b) mentioned that mineral supplementation on Simmental cows using the different forms (meal and block) did not affect blood protein.…”
Section: Blood Biochemical Hematological and Mineral Profilementioning
confidence: 99%